Interactive effect of salinity and two nitrogen fertilizers on growth and composition of sorghum - E. Esmaili; S.A. Kapourchal; M.J. Malakouti; M. Homaee (Plant, Soil and Environment, 2008)
The objective of this study was to investigate the interactive effects of salinity and different sources of applied N on growth, yield and nutrient composition of sorghum. The salinity treatments C0, C1, C2, C3 and C4 corresponded to 0.6, 6, 8, 10 and 12 dS/m, respectively. Eight fertilization treatments combined urea and ammonium nitrate sources. The height, fresh weight, dry weight, leaf area, N, K, Ca, Mg, Na and Cl contents of treated plants were measured after harvesting. Results indicate that both emergence and growth were significantly decreased by increasing salinity. The plant response to N fertilizers appeared to be different at each salinity level. The maximum production of C0 treatment was obtained for N-3, while at C1 and C2 treatments the maximum yield was obtained for N-2 and N-1 treatments, respectively. In the saline treatments, there was no significant difference between the two applied N-sources. The N, Ca, Mg, Na and Cl concentrations in plant tissues increased with increasing salinity; K concentration and the uptake of N, K, Ca and Mg were however decreased.